ANALISIS KESEHATAN KOPERASI JASA KEUANGAN SYARIAH MENGGUNAKAN METODE CAMEL PADA BAITUTTAMWIL TAMZIS WONOSOBO - Fauzia Ratih Ismaya; Hari Susanta Nugraha`; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2014)
This research aims to assess wealth of BMT Tamzis Wonosobo by using CAMEL method during a period of time of 2008 to 2012. Camel method has five aspects, which are Capital Adequacy Ratio (CAR), earning asset quality ratio (KAP) and Provision For Loan Losses (PPAP), management, asset earning power and operational independency ratio, and liquidity, cash and loan to deposit ratio. This research is a quantitative one and is guided by Keputusan Menteri Negara Koperasi dan Usaha Kecil dan Menengah Republik Indonesia No. 96/Kep.M.KUKM/IX/2004 about Standardized guide on Operational Management for Saving And Loan Cooperation and Cooperation’s Saving And Loan Unit. This research use both qualitative data from interview as well as quantitative data obtained from financial report of BMT Tamzis Wonosobo.The result and discussion of all CAMEL’s factor is healthy except on earning power factor, however, Asset Earning Power Ratio is low because too high growth in fixed assets. Conclusion and suggestion based on CAMEL method suggest that it gains healthy status from 2008 to 2012 because its credit value is more than 81 which is 92.95 at 2008 to 2011 and 90.45 at 2012 due to the decreased earning power factor. It is suggested for BMT Tamzis Wonosobo to enhance its asset quality that supports good health level, optimalize fund gathering and allocating effectively and efficiently. Another suggestion would be for BMT Tamzis to sustain its health level by increasing ratio value of each of CAMEL factors. Things need to be concern about, in this case, is earning power ratio because seeing from its percentage weight, this ratio is very dominating.